The Impact of Value Chain Analysis Implementation on Competitive Advantage in Coffee Shop Businesses in Mataram City - Agustinawati Agustinawati; Animah Animah (International Journal of Business and Quality Research, 2024)
This study aims to analyze the influence of the value chain on competitive advantage in Coffee Shops in Mataram City. The value chain is considered crucial in achieving competitive advantage in business. The study collects primary data through a questionnaire involving 40 respondents who are coffee shop owners in Mataram City. To examine the impact of the value chain on competitive advantage, this study utilizes regression analysis with PLS 4 as the analytical tool. The findings of this study suggest that the value chain does not significantly influence the competitive advantage of coffee shops in Mataram City. This implies that improving the coffee value chain in Mataram City does not necessarily enhance its competitive advantage. Additionally, the study indicates that the value chain alone is not the sole determinant of competitive advantage. Therefore, coffee business owners in Mataram City should focus on enhancing other strategies such as marketing, menu innovation, excellent customer service, meeting local consumer preferences, and adapting to evolving market trends and customer preferences.